Canoeing - Owings, Lisa; Sabelko, Rebecca; Sowers, Laura (Minneapolis, MN, Bellwether Media Inc., 2023)
"Relevant images match informative text in this introduction to canoeing. Intended for students in kindergarten through third grade"-- Provided by publisher.
Includes index
Bibliography: page 23
Ages 5-8
Grades 2-3
Keywords: Canoes and canoeing; Canoes and canoeing -- Juvenile literature